2019
DOI: 10.1186/s12889-019-7847-1
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal visits are positively associated with uptake of tetanus toxoid and intermittent preventive treatment in pregnancy in Ivory Coast

Abstract: BackgroundMalaria and tetanus infections among pregnant women represent two major public health problems in sub-Saharan Africa. Optimum use of Intermittent preventive treatment in pregnancy (IPTp) with sulfadoxine-pyrimethamine (IPTp-SP) and immunization against tetanus among pregnant women during antenatal care (ANC) visits are recommended strategies to prevent these issues. Despite these recommendations, many women in Africa remain deprived of these cost-effective and life-saving interventions. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
32
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 63 publications
(46 reference statements)
9
32
3
1
Order By: Relevance
“…In the current study, we also provided evidence household wealth quintile had no effect on receiving adequate doses of TT immunization when compared to those with the poorest wealth quintile. This finding is contrary to previous studies done in Ivory Coast and in Pakistan [26,32,34,35]. We perceive that women from wealthy households have the financial means to seek healthcare services than those from poor households.…”
Section: Discussioncontrasting
confidence: 98%
“…In the current study, we also provided evidence household wealth quintile had no effect on receiving adequate doses of TT immunization when compared to those with the poorest wealth quintile. This finding is contrary to previous studies done in Ivory Coast and in Pakistan [26,32,34,35]. We perceive that women from wealthy households have the financial means to seek healthcare services than those from poor households.…”
Section: Discussioncontrasting
confidence: 98%
“…In this study, parity was found less likely to promote TT vaccine uptake, which is congruent to ndings from Nigeria, were parity had no any statistical association with TT vaccine uptake (21). However, the ndings is contrary to what was reported by Yaya and colleagues (10) in their study from Ivory Coast, were parity increased the odds of TT vaccine uptake. It is further claimed that parity of the woman promotes maternal healthcare utilization (29).…”
supporting
confidence: 62%
“…After adjusted for confounders, predictors of uptake of tetanus vaccination were early antenatal booking (AOR = 1.174 at 95% CI = 1.033-1.335, p = 0.014), age group of women [ to 34 years (AOR = 1.433 at 95% CI = 1.155-1.778, p = 0.001), more than 34 years (AOR = 1.379 at 95% CI = 1.065-1.786, p = 0.015)], wealth index [ rich (AOR = 1.261 at 95% CI = 1.083-1.468, p = 0.003)], parity [para 2-4 (AOR = 0.401 at 95% CI = 0.343-0.468, p < 0.001), para 5 and above (AOR = 0.217 at 95% CI = 0.178-0.265, p < 0.001)], level of education [ primary level, (AOR = 0.864 at 95% CI = 0.754-0.99, p = 0.035)] zones [Unguja Zanzibar Island (AOR = 0.434 at 95% CI = 0.309-0.609, p < 0.001), Pemba (Pemba Island) (AOR = 0.34 at 95% CI = 0.226-0.512, p < 0.001)] and adequate ANC visits (AOR = 0.649 at 95% CI = 0.582-0.723, p < 0.001) Table 3 Antenatal care service utilization have been recognized important approach to improve uptake of TT vaccine among women of reproductive age (10,13). Our study showed that early ANC booking determines the uptake of TT vaccine.…”
mentioning
confidence: 99%
“…Most of our findings are, however, consistent with the literature on uptake of other prenatal vaccines (eg tetanus toxoid and hepatitis B), even though the literature is mainly from Africa and Asia. Compared with no antenatal visit, Iqbal et al, 69 Yaya et al 70 and Roosihermiatie et al 71 all found that antenatal visits were associated with significantly increased tetanus toxoid vaccination among pregnant women in Pakistan, Ivory Coast and Indonesia, respectively. Frequent visits to a physician have been shown to be associated with increased receipt of SIV and may explain the association found between receipt of prenatal care and increased SIV uptake.…”
Section: Discussionmentioning
confidence: 99%